2022
DOI: 10.32604/phyton.2022.017981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Exponential Fertilization on Growth and Nutrient Concentration of Hydrangea macrophylla Seedlings

Abstract: Slow growth rate restricts the development and growth of seedlings due to nutrients deficiency or nutrient imbalance. Exponential fertilization can enhance the internal nutrient reserves in seedlings at the nursery-stage and strengthen their resistance to adverse conditions. In this study, nitrogen requirements for producing Hydrangea macrophylla 'Hanatemari' that robust seedlings, nutrient dynamics, biomass and growth, was examined utilizing exponential fertilization. The potted seedlings were fertilized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Ser. [8], and Pinus banksiana Lamb. [9] are more efficient in transporting nutrients under the exponential fertilization method.…”
Section: Introductionmentioning
confidence: 99%
“…Ser. [8], and Pinus banksiana Lamb. [9] are more efficient in transporting nutrients under the exponential fertilization method.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the exponential fertilization not only met the nutritional requirements of Quercus nuttallii seedlings, but also promoted the growth of seedlings and their root systems, and indirectly accelerated the accumulation of N/P/K, thus improving the quality of the plantation. Wang et al [14] investigated the nitrogen requirements of Hanatemari grown with exponential fertilization to enhance robust seedlings, nutrient dynamics, biomass, and growth. The study showed that exponential fertilization with reasonable regulation of fertilizer applied improves the quality of seedlings.…”
Section: Introductionmentioning
confidence: 99%